VALUE BASIS OF THE FORMATION OF THE NATIONAL ECONOMIC STRATEGIES: ABOUT THE METHODOLOGY OF BREAKTHROUGH IN THE POST-CRISIS WORLD - Задорожний, Г. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
Breakthrough strategy in the post-crisis world requires a fundamental change in the format of economic thinking, transfer it to the values coordinate of personal life. Family, education, social partnership - the fundamental basis of the strategy of the revival of the country for the good of man, its development and self-realization.